Coating Indwelling Urinary Catheter with Antibiotics Reduces Catheter-Associated Urinary Tract Infections (World Journal of Experimental Biosciences, 2020)
Catheter-associated urinary tract infections (CAUTIs) are a common and significant healthcare-associated infection and represent the serious complicating bacterial infectious diseases. In the present review, the role of coating indwelling catheters with antibiotics in reducing the complicating bacterial infection, especially in critical urinary tract infections. There different urinary catheters are used to help patients that suffering from defects in the urination process. Different antibiotics were used in coating the indwelling urinary catheter (IUC) such as Gentamicin, Fluoroquinolones (Nitrofurazone, Norfloxacin, Ciprofloxacin, Sparfloxacin), and Triclosan. The effectiveness of coating IUC with antibiotics was dependent on the patient’s clinical cases, the type of IUC, and the kind of antibiotic that would be used in the coating procedure. There are many restrictions in using the antibiotic coating IUC such as the producing the resistance strains and producing the allergy in patients. That is why, it is suggested to use antibiotic coating IUC is limiting in the serious CAUTIs.